Partitioned fluid-structure interaction techniques applied to the mixed-elastohydrodynamic solution of dynamically loaded connecting-rod big-end bearings - Profito,FJ; Zachariadis,DC; Dini,D (Tribology International, 2019)
The present contribution proposes different partitioned techniques, which are commonly used in fluid-structure interaction (FSI) applications, in the context of tribological simulations of the transient mixed-elastohydrodynamic problem of dynamically loaded connecting-rod bearings. With the premise that the FSI framework developed is general, in the current work the fluid flow effects have been considered through the averaged Reynolds equation by Patir & Cheng and the mass-conserving Elrod-Adams cavitation model. The multiphysics simulation framework developed has been used to simulate the connecting-rod big-end bearings of both heavy-duty diesel and high-speed motorcycle engines. In the latter case, the influence of polymer concentration in VM-containing oils with similar HTHS150 values on the bearing power loss is investigated and discussed in details.